1982
DOI: 10.2337/diab.31.1.s30
|View full text |Cite
|
Sign up to set email alerts
|

Yucatan Miniature Swine as a Model for the Study of Human Diabetes Mellitus

Abstract: Two lines of Yucatan miniature swine have been developed by genetic selection for decreased and increased glucose clearance during an i.v. glucose tolerance test. The decreased glucose clearance is due to low peripheral insulin levels usually from a decrease in insulin secretion. In two pigs the decreased peripheral insulin resulted from increased hepatic uptake of insulin. During gestation and lactation, an increased insulin resistance and a diabetic-like state occurs in some animais. When fed a low fiber die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Swine have been used extensively as a model of human in biomedical researches such as cardiovascular, metabolic and transplantation (Phillips et al, 1982;Larsen and Rolin, 2004;Imai et al, 2006;Groth, 2007). In the last decade, an increasing number of studies in the field of neuroscience has been reported (Lind et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Swine have been used extensively as a model of human in biomedical researches such as cardiovascular, metabolic and transplantation (Phillips et al, 1982;Larsen and Rolin, 2004;Imai et al, 2006;Groth, 2007). In the last decade, an increasing number of studies in the field of neuroscience has been reported (Lind et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pigs are, like man, recognised as an LDL species (Olsen et al 2002), and they transport a large part of their esterified cholesterol in this lipoprotein. Pigs are also omnivorous (Phillips et al 1982), their cardiovascular system is quite similar to that of man (Dixon et al 1999), and their human-like physiology (Moughan et al 1992) and physiopathology related to obesity, type 2 diabetes and CVD (Dixon et al 1999), as well as their large size, are very useful for mimicking the situation of obese people. The objective of the present study was to observe possible specific lipid -lipoprotein modulation in relation to the development of obesity induced during sexual maturation in a Yucatan mini-pig model of childhood obesity.…”
mentioning
confidence: 99%
“…Adult mini-pigs have already been used to study insulin resistance and lipid metabolism changes in relation to the Western lifestyle (Phillips et al 1982;Gerrity et al 2001). Even if pigs and mini-pigs, compared with man, have a very low activity of CETP and present low triacylglycerol plasma concentrations Olsen et al 2002), compared with mice and rats, pigs and mini-pigs represent one of the species most relevant for modelling lipoprotein metabolism in man.…”
mentioning
confidence: 99%
“…The mechanisms underlying the increased risk and greater acceleration and severity of atherosclerotic disease in diabetes remain an enigma due, at least in part, to the lack of suitable humanoid animal models (5,6). In this study, we chose to induce diabetes in an atherosclerotic swine model, which we have extensively characterized over the last two decades (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%